Salt and Aldosterone – Reciprocal and Combined Effects in Preclinical Models and Humans - Chen, Li; Adolf, Christian; Reincke, Martin; Schneider, Holger (Hormone and Metabolic Research, 2023)
Primary aldosteronism is an endocrine disorder caused by excessive production of aldosterone by the adrenal glands, and is recognized as the most important cause of endocrine hypertension. With specific therapy, this type of hypertension is potentially curable. In the general population, high salt intake increases the risk for cardiovascular diseases like stroke. In populations with aldosterone excess, observational and experimental data suggest that aldosterone-induced organ damage requires a combination of high dietary salt intake and high plasma aldosterone, i.e., plasma aldosterone levels inappropriately high for salt status. Therefore, understanding the relationship between plasma aldosterone levels and dietary salt intake and the nature of their combined effects is crucial for developing effective prevention and treatment strategies. In this review, we present an update on findings about primary aldosteronism and salt intake and the underlying mechanisms governing their interaction.
Keywords: sodium; mineralocorticoid; DOCA; salt restriction; inflammation; cardiovascular damage